INCREASING GROSS REGIONAL PRODUCT THROUGH ENHANCING THE QUALITY OF EDUCATIONAL SERVICES (International journal of artificial intelligence, 2025)
This article explores the relationship between improving the quality of educational services and increasing gross regional product, focusing on Uzbekistan’s regional economies. It examines how investments in education quality, such as teacher training, modern curricula, and digital learning tools, can enhance human capital, drive productivity, and boost economic output. Statistical data from official sources indicate that regions with higher education investments experienced significant GRP growth. Drawing on human capital theory and global case studies, the study addresses challenges like resource disparities and outdated infrastructure. Recommendations include public-private partnerships and targeted education reforms to maximize economic impact.